Action Video Gaming Experience Related to Altered Resting-State EEG Temporal and Spatial Complexity - Cui, Ruifang; Jiang, Jinliang; Zeng, Lu; Jiang, Lijun; Xia, Zeling; Dong, Li; Gong, Diankun; Yan, Guojian; Ma, Weiyi; Yao, Dezhong (Frontiers in Human Neuroscience, 2021)
Action video gaming (AVG) places sustained cognitive load on various behavioral systems, thus offering new insights into learning-related neural plasticity. This study aims to determine whether AVG experience is associated with resting-state electroencephalogram (rs-EEG) temporal and spatial complexity, and if so, whether this effect is observable across AVG subgenres. Two AVG games – League of Legends (LOL) and Player Unknown’s Battle Grounds (PUBG) that represent two major AVG subgenres – were examined. We compared rs-EEG microstate and omega complexity between LOL experts and non-experts (Experiment 1) and between PUBG experts and non-experts (Experiment 2). We found that the experts and non-experts had different rs-EEG activities in both experiments, thus revealing the adaptive effect of AVG experience on brain development. Furthermore, we also found certain subgenre-specific complexity changes, supporting the recent proposal that AVG should be categorized based on the gaming mechanics of a specific game rather than a generic genre designation.